Developing and sustaining sport psychology programs : a resource guide for practitioners - Maher, Charles A., 1944- (New York, NY : Routledge, 2020)
"Developing and Sustaining Sport Psychology Programs: A Resource Guide for Practitioners outlines a systemic approach to creating comprehensive, sustainable sport psychology programs in professional sports organizations, colleges and universities, and secondary school levels. Based on the author's more than thirty years of professional experience, this volume presents a framework that delineates methods for designing, implementing, and evaluating sport psychology programs, discussing topics such as needs assessment and client identification. Featuring real-world experiences and clear, non-technical writing, this step-by-step guide can be applied to a range of sport psychology programs including mental skills, life skills, coach education, leadership training, and team development programs. Developing and Sustaining Sport Psychology Programs details a program development process that has been applied successfully at the professional, collegiate, and secondary school levels over a more than thirty-year period. It has contributed to the development of sport psychology programs that have sustained themselves over the course of time, and is an essential text for sport psychologists and mental skills coaches at all levels as well as graduate students and other professionals in the field"--
Taking a systems perspective on sport psychology -- Defining and illustrating sport psychology programs -- Setting the stage for program development -- Overviewing the program development process -- Specifying the program participants -- Assessing the needs of program participants -- Determining relevant organizational context -- Establishing the purpose and goals of the program -- Organizing the program design -- Putting the program design into an evaluable form -- Facilitating program implementation -- Monitoring the process of program implementation -- Formulating a program evaluation plan -- Evaluating program implementation -- Evaluating goal attainment -- Evaluating reactions to the program -- Evaluating the program's strong points and limitations -- Communicating and using program evaluation information -- Closing comments and program development practice standards.
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- Psychological aspects; Athletes -- Mental health services -- Planning; SPORTS & RECREATION / Sports Psychology; PSYCHOLOGY / Applied Psychology; SPORTS & RECREATION / Coaching / General